Alternative schemes of financing training - Gasskov, Vladimir [Herausgeber] (International Labour Office, 1994)
"There is a growing interest in both industrialized and development countries in studying and reforming national systems of financing technical and vocational education and training (TVET). Based on examples of countries and industries that have developed innovative arrangements, this book addresses several issues related to financing TVET, including co-financing by governments, employers and workers. Many diverse TVET financing mechanisms exist, and each sends selective signals to ist beneficiaries. The study examines both successful and unsuccessful examples of new practices, including schemes for funding public education and training, as well as apprenticeships, various types of levy-based schemes and income tax rebate incentives. The case studies contain technical details which will help policy-makers to make better decisions. The book ends with a checklist for evaluating your own system of financing TVET." (author's abstract, IAB-Doku)

Der Bericht stellt unterschiedliche Modelle und Instrumente der Finanzierung von Berufsausbildung und Fachausbildung vor, die in den letzten Jahren in einer Reihe von Industrieländern und Entwicklungsländern in Zusammenarbeit von Regierungen, Arbeitgebern und Arbeitnehmern entwickelt und angewandt wurden. In Fallstudien werden konkrete Regelungen und Erfahrungen in verschiedenen Bereichen der Berufs(aus)bildung und in verschiedenen Ländern beschrieben und bewertet. Den Abschluss bildet eine Prüfliste, das zur Evaluation des eigenen Finanzierungssystems beruflicher Bildung genutzt werden kann. (IAB) Aus dem Inhalt: A. Alternative sources of financing TVET B. New schemes of financing public TVET C. Renue-generating levy schemes D. Levy-exemption, levy-grant and reimbursement schemes E. Income tax rebate training incentives F. Financing apprenticeship G. Evaluate your system of financing TVET
Alternative Modelle zur Finanzierung von beruflicher Bildung
Keywords: S 1 Stufen der Berufsbildung; S 4 Kosten & Finanzierung; S 3.5.4 Sozialpartner; S 1.3 Berufliche Erstausbildung; T 4.4 Politikwissenschaften; G 2.1.1 Ökonomie / Märkte; I 2.1.4 Ballungsgebiete; I 2.3 Außereuropäische Regionen; Berufsbildung; Finanzierung; Berufsausbildung; Betriebliche Berufsausbildung; Sozialpartner; Berufsbildendes Schulwesen; Internationaler Vergleich; Ausbildung; Kosten; Ausbildungsinvestition; Staat; Privatwirtschaft; Quantitative Angaben; Industrieländer; Entwicklungsländer